"Changing ourselves, changing others" : an analysis of the life stories of participants in a training course for volunteers within a non-governmental organisation in the Eastern Cape Province of South Africa - Harper, Christopher Duncan (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
Gender-based violence has been recognized as a pressing mental health problem that is prevalent within South African society. Non-governmental organizations play a major role in addressing and highlighting the issue. These organizations make use of volunteers in order to assist in meeting their goals. The modernist perspective has been the dominant investigative mode when research into volunteers has been conducted. However, this study has been conducted with an emphasis on narrative. In its use of this constitutionalist and deconstructive perspective, it examines the identity of the research participants within the dominant social and cultural discourses that story their lives. This presents a major challenge to the modernist framework. In examining the life stories of the participants an emergent nature of identity is noted. Through the process of storying their lives and ascribing meaning to their experiences and understandings, the participants engaged in a process of constructing their identity. This research recognizes that identity is both multi-sited and multi-storied. The emphasis on personal agency enables the participants to restory their lives in the light of challenging prevailing discourses. It is in this process of challenge that they reauthor their lives and are in a position to change their own lives and the lives of others.
Keywords: Non-governmental organizations -- South Africa -- Eastern Cape; Violence -- South Africa -- Eastern Cape; Abused women -- Counseling of; Women -- Crimes against -- South Africa; Volunteers